Use of Gas Chromatography and SPME Extraction for the Differentiation between Healthy and Paenibacillus larvae Infected Colonies of Bee Brood—Preliminary Research - Bartosz Piechowicz; Aleksandra Kwiatek; Stanisław Sadło; Lech Zaręba; Anna Koziorowska; Daniela Kloc; Maciej Balawejder (Agriculture, 2023)
Paenibacillus larvae is a deadly pathogen for bee brood, which can lead to the death of entire colonies. The presence of specific volatile organic compounds (VOCs) in the hive may be related to the occurrence of this bacterium in brood. Compositions of those volatile fractions present in healthy brood from control colonies and the brood without symptoms of infection collected from the colonies infected by P. larvae were compared using gas chromatography coupled with mass spectrometry (GC-MS) and solid phase microextraction (SPME). Among the seven compounds detected and quantified, the relative concentrations of 3-carene and limonene significantly differentiated the brood from healthy and infected colonies. Based on the ratio analysis, the samples were differentiated in terms of the number of emitted VOCs.